Kemampuan Manajerial Kepala Madrasah dalam Meningkatkan Mutu Lembaga - Chasnawati, Muthik (Taallum: Jurnal Pendidikan Islam, 2014)
A principal of madrasah must have good managerial skill related to planning, organizing, staffing, coordinating, and controlling the school. With this skill, it is hoped that madrasah will stand equally with formal schools in order to develop human resources in Indonesia to achieve quality society.